ChemInform Abstract: Pd‐Catalyzed Decarboxylative ortho‐Acylation of O‐Methyl Oximes with Phenylglyoxylic Acids. Issue 23 (16th May 2013) - Yang, Zhiyong; Chen, Xiang; Liu, Jidan; Gui, Qingwen; Xie, Kai; Li, Miaomiao; Tan, Ze
Abstract Twenty examples of the title reaction using (NH4)2S2O8 as the oxidant are presented.